Production of Red Palm Oil Based Spread Base Rich in Carotene through Enzymatic Interesterification in Batch-type Reactor. - Wibowo, Mario (2010)
Interesterification of red palm oil (red palm olein/RPO and red palm stearin/RPS) and coconut oil (CNO) blends of varying proportions using a nonspecific immobilized Candida antartica lipase (Novozyme 435) was studied for the production of spread base. The interesterification reaction was held in a batch-type reactor. Two substrate blends were chosen for the production of spread base: 77,5:22,5 and 82,5:17,5 (RPO/RPS:CNO, by weight) through enzymatic interesterification in three different reaction times (2, 4, and 6 hours). RPO/RPS ratio was 1:1. Interesterification reactions were studied at 60oC at constant weight ratio (10%) of Novozyme 435. The reaction was carried out at steady agitation (200 rpm). The interesterified blends were evaluated for their physical characteristics (solid fat content/SFC and slip melting point/SMP) and chemical characteristics (moisture content, free fatty acid/FFA content and carotene retention). The results showed that all of the interesterified mixtures have a lower SFC and SMP values compared with the initial mixtures. SMP values and SFC increased in a longer reaction. SMP values were ranging from 30,8oC to 34,9oC. The moisture content and FFA content increased in a longer reaction. Carotene retentions were ranging from 74,80% to 81,08%. This study indicated that interesterified products have desirable physical properties for possible use as spread base rich in carotene.